A influência dos aplicativos móveis no negócio das empresas prestadoras de serviço de táxis em São Paulo: um estudo de caso - Vilas Bôas, Andréa Silva (2016)
This work intends to identify the relevant changes in the market and what the value realized by customers and cabbies, considering the insertion of the companies providing taxi service in the virtual world by using apps. In order to reach out this goal, we explain the value chain concept, including the virtual value chain and value network, aiming to get the best knowledge of the structure in which the companies of this new environment are based on, as well as we explain the business model concepts and Business Model Canvas. Based on this theoretical foundation, we propose a framework that will allow extract information and, after analyzing them, we identify, through a case study, the relevant changes that have occurred in this market and the value realized by both customers and cabbies. The topic is relevant because this is a significant change in how the companies make relationship with their customers and providers. And because it allows to observe what added value this model has been providing and why, due to this, about 30 thousands cabbies in the existing 35 thousands in São Paulo have opted for using apps, making that one of the companies studied in this work have get to more than 2.5 million of downloads in the whole Brazil. It is expected, through this study, to identify the relevant changes that the apps integration has brought to the users and taxi drivers and provide a framework that can be used as an assistant in the analysis of the value chain and virtual value chain of the market for taxi services and show that this model is not just fading to which we can assign a number of benefits, but also a trend that is redefining the format of the companies in this market.